The Educational Inspection facing the innovation - Estefanía Lera, José Luis (Avances en Supervisión Educativa, 2017)
The great subject of our educational system is the generalized implementation of new methodologies in line with the times in which we live. Methodology, which puts the emphasis on "learning" about "teaching" and helping students to acquire the skills and practical know-how necessary to develop in our knowledge society, therefore innovation is necessary in a structural way.And in this challenge that has to face our educational system must be involved all the educational actors: Central and autonomous Administration, educational centers and teachers, educational community and educational inspection. Each one of them collaborating in the functions that it has entrusted and of which they are responsible.It is necessary a methodology that breaks with the routine of a teaching merely transmitting knowledge accumulation, which entails a new role of the role of the teacher, and a different conception of the training of the students more practical and useful, more motivating and contextualized.The educational inspection for the important place it occupies between the norm and the reality constitutes a fundamental actor of this necessary change.
Keywords: innovation; methodological change; teaching staff; educational inspection